Multilocus sequence analysis for Leishmania braziliensis outbreak investigation. - Mariel A Marlow; Mariana C Boité; Gabriel Eduardo M Ferreira; Mario Steindel; Elisa Cupolillo (Public Library of Science (PLoS), 2014)
With the emergence of leishmaniasis in new regions around the world, molecular epidemiological methods with adequate discriminatory power, reproducibility, high throughput and inter-laboratory comparability are needed for outbreak investigation of this complex parasitic disease. As multilocus sequence analysis (MLSA) has been projected as the future gold standard technique for Leishmania species characterization, we propose a MLSA panel of six housekeeping gene loci (6pgd, mpi, icd, hsp70, mdhmt, mdhnc) for investigating intraspecific genetic variation of L. (Viannia) braziliensis strains and compare the resulting genetic clusters with several epidemiological factors relevant to outbreak investigation. The recent outbreak of cutaneous leishmaniasis caused by L. (V.) braziliensis in the southern Brazilian state of Santa Catarina is used to demonstrate the applicability of this technique. Sequenced fragments from six genetic markers from 86 L. (V.) braziliensis strains from twelve Brazilian states, including 33 strains from Santa Catarina, were used to determine clonal complexes, genetic structure, and phylogenic networks. Associations between genetic clusters and networks with epidemiological characteristics of patients were investigated. MLSA revealed epidemiological patterns among L. (V.) braziliensis strains, even identifying strains from imported cases among the Santa Catarina strains that presented extensive homogeneity. Evidence presented here has demonstrated MLSA possesses adequate discriminatory power for outbreak investigation, as well as other potential uses in the molecular epidemiology of leishmaniasis.